Gender and youth lens for inclusive financial solutions - DuttaGupta, Tanaya; Vyas, Shalika (International Livestock Research Institute, 2025)
As part of a learning event in partnership with African Rural and Agricultural Credit Association (AFRACA) and CIAT, this session focused on integrating a gender and youth lens for inclusive climate finance solutions. The learning event convened senior professionals from various financial institutions for an intensive, practice-oriented exchange. The aim of this session in particular was to build capacity of the institutions for inclusive and tailored design and delivery of financial solutions. During the session, participants engaged in co-designing solutions for diverse personas (e.g., married pastoral woman, unmarried young woman in business, women’s group, and youth trader).